Garbage-man-in-the-middle (type 2) attack on the Lucas based El-Gamal cryptosystem in the elliptic curve group over finite field - Sarbini, Izzatul Nabila; Wong, Tze Jin; Koo, Lee Feng; Othman, Mohamed; Md. Said, Mohamad Rushdan; Yiu, Pang Hung (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
Garbage-man-in-the-middle (type 2) attack is one of the various homomorphic attacks based on its homomorphism nature of cryptosystem. The idea of this attack relies on the possibility to access to the “bin” of recipient. This type of attack requires an access to the “bin” in order to recover the original plaintext. In this paper, an investigation was carried out to evaluate the nature of a homomorphic attack on the Lucas based El-Gamal Cryptosystem in the Elliptic Curve Group over finite field. The result shows that the cryptanalyst is able to obtain the plaintext without knowing the secret number, a, b and R, providing that the receiver decrypts the ciphertexts with a faulty decryption key.